The magic strings of Frankie Presto - Albom, Mitch (London : Sphere, 2015)
At nine years old, Frankie Presto is sent to America in the bottom of a boat with only an old guitar and six precious strings. His amazing journey weaves him through the musical landscape of the twentieth century, with his stunning talent impacting numerous icons along the way, including Hank Williams, Elvis Presley, Carole King and even KISS. Frankie makes records and is adored. But his gift is also his burden, as he realises, through his music, he can affect people's futures - with one string turning blue whenever a life is altered. Then, at the height of his popularity, Frankie Presto vanishes and his legend grows. Only decades later does he reappear, to change one last life... - Publishers description
Keywords: Guitarists -- Fiction; Popular music -- Fiction; Ability -- Fiction